TALABALARNING ISHLAB CHIQARISHDAGI AMALIY MASHG‘ULOTLARINI QO‘LLAB-QUVVATLASH - Mamatov, D.N. (SCIENCE and SOCIETY, 2022)
Production is recorded in standards for each content area, as well as in national standards for learners. Words such as “correction”, “design”, “creation”, “modeling”, “development” and “reporting” are important aspects of student learning in terms of content, including student learning and production, and many other manufacturing projects. standards, communication, collaboration, and other learning objectives.
Keywords: production; education system; students; science integration